Copper-catalyzed Beckmann-type fragmentation of less-strained cycloketoxime esters. Issue 12 (14th April 2021) - Zhao, Binlin; Zheng, Yukun; Chen, Cheng; Wang, Mengning; Ma, Mengtao; Shi, Zhuangzhi
Abstract : We have developed a modular, convenient and practical copper-catalyzed platform for the preparation of alkene nitriles from corresponding cycloketoxime esters via radical-mediated C–C bond cleavage. Abstract : We have developed a modular, convenient and practical copper-catalyzed platform for the preparation of alkene nitriles from corresponding cycloketoxime esters via radical-mediated C–C bond cleavage. A broad scope of cycloketoxime esters (4-membered to 8-membered) and some complex substrates derived from natural product derivatives performed well, affording corresponding ring opening products in the presence of copper salts. Moreover, the etherification, oxidation and alkynylation of cycloketoxime esters could also be achieved under variable copper-catalyzed conditions.